Exploring the effectiveness of ISO 14001 in local authorities - Campbell, Marion (Cranfield University, 2004)
In this study the effectiveness of the implementation of ISO 14001 by Local Authorities is explored, as are the factors that hinder and/or further implementation of the standard. These include the motivations for applying the standard, its strengths and weaknesses and the consistency of it use. The research was undertaken using interviews both of key informants in a variety of councils and of those in a detailed case study of Bedfordshire County Council. The research suggests that consistency of application between different councils was poor and the motivations were mainly environmentally based, and its strengths and weaknesses, although varied, had few consistent factors as perceived by the respondents. The main strengths of ISO 14001 included flexibility and the demand for continual improvement, and its main weaknesses being the opportunity that flexibility provides for abuse of the standard.